(untitled) (Dhaka University Journal of Biological Sciences, 2014)
A comparative analysis between parental and childrens attitude toward homework for three grade levels (Grade?III, V and VII) reveals the importance of homework in educational experience. Two hundred sixty parents (140 mothers and 120 fathers) and 260 children (148 girls and 112 boys) of different schools in Dhaka city responded to parent and children forms of attitude toward homework questionnaire. Chi square value indicated common agreement between the children and the parents attitude toward homework. Certain dimension of childrens attitude differed for grade levels and gender. The study also focused on the effect of homework on family relationship and general attitude toward school. DOI: http://dx.doi.org/10.3329/dujbs.v23i1.19830 Dhaka Univ. J. Biol. Sci. 23(1): 77-83, 2014